2006
DOI: 10.1002/pon.1074
|View full text |Cite
|
Sign up to set email alerts
|

A family‐based model to predict fear of recurrence for cancer survivors and their caregivers

Abstract: Although fear of cancer recurrence is a great concern among survivors and their families, few studies have examined predictors of fear of recurrence. The purpose of this study was to identify factors associated with fear of recurrence in a population-based sample (N = 246) and determine if survivors and family caregivers influenced one another's fear of recurrence. A family framework guided the study and analyses included multilevel modeling using the Actor-Partner Interdependence Model. Results indicated that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

17
220
2
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 156 publications
(240 citation statements)
references
References 47 publications
(73 reference statements)
17
220
2
1
Order By: Relevance
“…Post-treatment fear of recurrence is wellrecognised in patients (Simard et al, 2010) but can also prove a significant difficulty for partners (Mellon et al, 2007), even when the patient has an optimistic outlook, as this study affirms. Recognising this, there has been suggestion of routinely involving caregivers in survivorship care planning (Given et al, 2011).…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…Post-treatment fear of recurrence is wellrecognised in patients (Simard et al, 2010) but can also prove a significant difficulty for partners (Mellon et al, 2007), even when the patient has an optimistic outlook, as this study affirms. Recognising this, there has been suggestion of routinely involving caregivers in survivorship care planning (Given et al, 2011).…”
Section: Discussionsupporting
confidence: 58%
“…Firstly, by adopting a multi-perspective qualitative methodology (Kendall et al, 2009), the study aimed to provide a more detailed analysis of patient-caregiver dyads, a gap identified in recent research (Fletcher et al, 2012;Hagedoorn et al, 2011;Mellon et al, 2006Mellon et al, , 2007Waldron et al, 2012). Secondly, it included both cancer patients and their caregivers after completion of treatment, a key transition period (Mellon et al, 2006;Murray et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…[95][96][97] Caregivers of individuals with recurrent breast cancer have reported as many adjustment problems as the survivors 97 and even greater levels of fear of recurrence, less social support, and poorer QOL than survivors. 73,98,99 These caregivers were troubled by depressive moods and stress in marital relationships. 100 Self-efficacy, social support, and family hardiness related positively to the QOL of family caregivers; whereas symptom distress, fear of recurrence, hopelessness, family stressors, and negative appraisal of illness or caregiving related negatively to the QOL of family caregivers.…”
Section: Middle-to Long-term Survivorship Phase With Remissionmentioning
confidence: 99%
“…For example, both cancer survivors and their caregivers frequently report elevated stress and fear of cancer recurrence, which have been associated with poor mental and physical health outcomes, decreased quality of life [3], and reduced adherence to follow-up care [4]. Research has also documented the interdependence of mental and physical health within survivor-caregiver dyads [5][6][7] and shown that dyadfocused approaches to reducing breast cancer patients' depressive symptoms may be more efficacious than individual-oriented approaches [8]. Thus, there is increasing interest in developing dyad-focused research studies and interventions that involve both breast cancer survivors and their caregivers [9].…”
Section: Introductionmentioning
confidence: 99%